Locoregional therapy in de novo metastatic breast cancer: Systemic review and meta-analysis. (August 2021) - Reinhorn, Daniel; Mutai, Raz; Yerushalmi, Rinat; Moore, Assaf; Amir, Eitan; Goldvaser, Hadar
Abstract: Background: Locoregional therapy (LRT) in de novo metastatic disease is controversial with inconsistent results from randomized control trials (RCTs). Methods: RCTs comparing LRT and systemic therapy to standard therapy alone in de novo metastatic breast cancer were identified. Hazard ratios (HRs) and their associated 95% confidence intervals (CIs) were computed and pooled in a meta-analysis using generic inverse variance. Overall survival (OS) and time to locoregional progression data were extracted for the intention to treat (ITT) population. Data on OS for pre-specified subgroups defined by tumor subtype and by site of metastases were also extracted. Results: Analyses included 4 trials comprising 970 patients. LRT included standard surgery to the primary breast tumor in all studies, and adjuvant radiation per standard of care was required in 3 studies. Compared to standard treatment, LRT was not associated with improved OS in the ITT population (HR 0.97, 95% CI 0.72–1.29, p = 0.81). However, LRT was associated with improved time to locoregional progression (HR 0.36, 95% CI 0.14–0.95, p = 0.04). LRT was not associated with improved OS in any tumor subtypes, including hormone receptor positive (HR 0.96, 95% CI 0.65–1.43), triple negative (HR 1.4, 95% CI 0.50–3.91) and human epidermal growth factor receptor 2 positive disease (HR 0.93, 95% CI 0.68–1.28). Additionally, LRT did not improve OS in bone only disease (HR 0.97, 95% CI 0.58–1.62) and in visceral disease (HR = 1.02, 95% CI 0.77–1.35). Our critical appraisal has identified some methodological problems in the design and conduct of the studies included that could affect the meta-analysis result. Conclusions: LRT in de novo metastatic breast cancer is not associated with improved OS. Results are consistent among different breast cancer subgroups. However, this conclusion should be interpreted with caution in view of the limitations identified in meta-analysis. Highlights: Locoregional treatment in de novo metastatic breast cancer does not improve survival. The effect of locoregional therapy is similar between tumor subtypes. Locoregional treatment does not improve survival in bone only or in visceral disease. Time to locoregional progression is significantly longer with therapy.